2015
DOI: 10.7554/elife.06845
|View full text |Cite
|
Sign up to set email alerts
|

H2A histone-fold and DNA elements in nucleosome activate SWR1-mediated H2A.Z replacement in budding yeast

Abstract: The histone variant H2A.Z is a universal mark of gene promoters, enhancers, and regulatory elements in eukaryotic chromatin. The chromatin remodeler SWR1 mediates site-specific incorporation of H2A.Z by a multi-step histone replacement reaction, evicting histone H2A-H2B from the canonical nucleosome and depositing the H2A.Z-H2B dimer. Binding of both substrates, the canonical nucleosome and the H2A.Z-H2B dimer, is essential for activation of SWR1. We found that SWR1 primarily recognizes key residues within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 33 publications
12
76
0
Order By: Relevance
“…Interactions with Asp 91 and Glu 93 of the H2A acidic patch anchor this module firmly on the face of the octamer. The acidic patch has previously been shown to be important for SWR1 histone 3 of 8 exchange (17). Similarly, we observe a loss in histone exchange activity when Arp6/Swc6 is deleted ( Fig.…”
Section: Other Contacts With the Nucleosomesupporting
confidence: 83%
See 2 more Smart Citations
“…Interactions with Asp 91 and Glu 93 of the H2A acidic patch anchor this module firmly on the face of the octamer. The acidic patch has previously been shown to be important for SWR1 histone 3 of 8 exchange (17). Similarly, we observe a loss in histone exchange activity when Arp6/Swc6 is deleted ( Fig.…”
Section: Other Contacts With the Nucleosomesupporting
confidence: 83%
“…Multiple contacts are made with the histone core and DNA wrap. The Swr1 subunit ATPase domains are located at the canonical SHL2 position seen in the structures of most other remodelers (19,20) and consistent with SWR1-nucleosome footprinting studies (17). There is clear density for a bound nucleotide (ADP• BeF 3 ) at the ATP-binding site ( fig.…”
Section: Interactions Between the Swr1 Atpase Domains And The Nucleosomesupporting
confidence: 77%
See 1 more Smart Citation
“…Overlays of the protection patterns of nucleosomes alone and bound to INO80 revealed the regions where INO80 stably interacts with DNA. We found that unlike NURF, ISW2, ISW1a, SWI/SNF and SWR1; INO80 does not stably bind to SHL−2, or two DNA helical turns from the dyad axis3948. Instead, INO80 interacts with nucleosomal DNA at SHL −3, −5 and −6 as seen by DNA footprinting protections centred at −33, −53 and −63 nucleotides (nt) from the dyad axis (compare Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Previously, remodeling activities for several chromatin remodelers were shown to require intact DNA at the internal SHL2 site on the nucleosome, which is ~50 bp from the closest edge of the nucleosome (McKnight et al, 2011; Ranjan et al, 2015; Saha et al, 2005; Schwanbeck et al, 2004; Zofall et al, 2006). Cross-linking studies with ISWI and SWI/SNF remodelers demonstrated that the ATPase motor of the remodeler bound to SHL2 (Dang and Bartholomew, 2007; Dechassa et al, 2012); however, the photoactivatable cross-linkers in those studies originated from DNA and therefore did not provide sufficient information for uniquely orienting the protein domains on the nucleosome.…”
Section: Resultsmentioning
confidence: 99%